DOES TEACHING PRACTICE EXPERIENCE AFFECT INTEREST IN BECOMING A TEACHER? THE ROLE OF SELF-EFFICACY AS AN INTERVENING VARIABLE - Nurcahyani, Sulis Rizkyka; Saptono, Ari; Pratama, Aditya (Transpublika Publisher, 2022)
This study aims to determine the effect of teaching practice experience on interest in becoming a teacher mediated by self-efficacy in education students at the State University of Jakarta. This study uses a quantitative approach and uses primary data. The population in this study were students of education at the State University of Jakarta with a total sample of 250 students who were guided by the Roscoe Theory of 10% of the total population and the sample technique used was proportional random sampling. This study shows the results that teaching practice experience has a positive and significant effect of 38,1% on interest in becoming a teacher, self-efficacy has a positive and significant effect of 30,6% on interest in becoming a teacher, teaching practice experience has a positive and significant effect of 39,6% of self-efficacy and the role of self-efficacy mediating between teaching practice experience of 12,1% of interest in becoming a teacher in education students at the State University of Jakarta. With the intervening variable in this study, it is able to be a liaison or intermediary between exogenous variables and endogenous variables so that it has a total value of 50,2%.